2003
DOI: 10.1055/s-2003-44593
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosing Colitis: a Prospective Study on Essential Parameters for Reaching a Diagnosis

Abstract: Segmental biopsy specimens are essential for the differential diagnosis of intestinal inflammation. Information on the endoscopic features and clinical data are useful in differentiating some forms of colitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0
30

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(65 citation statements)
references
References 12 publications
0
35
0
30
Order By: Relevance
“…A study by Dejaco et al showed that the accuracy of diagnosing colitis increases from 66% to 92% when segmental biopsies are taken rather than two biopsies throughout the colon. 4 Rectal biopsies are necessary to either conirm or reject rectal involvement and may be additionally helpful in differentiating IBD from other inlammatory lesions.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Dejaco et al showed that the accuracy of diagnosing colitis increases from 66% to 92% when segmental biopsies are taken rather than two biopsies throughout the colon. 4 Rectal biopsies are necessary to either conirm or reject rectal involvement and may be additionally helpful in differentiating IBD from other inlammatory lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Zurzeit werden keine Spezialverfahren (Immunhistochemie, andere Techniken) für die Routine verwendet [191,192]. Der Nutzen multipler Biopsien aus verschiedenen Regionen des unteren GI-Traktes zur Diagnosesicherung eines M. Crohn ist in der Literatur belegt [168,170,193,194].…”
Section: Postoperative Diagnostikunclassified
“…This has been demonstrated for inflammatory diseases such as chronic idiopathic inflammatory bowel diseases (IBD) and for neoplastic diseases. [9] Therefore different guidelines for endoscopic sampling in various diseases have been developed. [10][11][12] ECCO guidelines propose to obtain "multiple" biopsies from five sites around the colon (including the rectum) and the ileum for a reliable diagnosis of Crohn's disease.…”
Section: Number Of Samplesmentioning
confidence: 99%
“…A diagnosis of Crohn's disease on endoscopic samples of the colon relies particularly on the analysis of multiple biopsies from different segments of the colon including the ileum. [68] Analysis of multiple biopsies yields a positive diagnosis of Crohn's disease in 64% of the cases compared to 24% for one single rectal biopsy. [64,69] Biopsies of the terminal ileum are mainly useful in patients with inflammatory diarrhoea.…”
Section: Inflammatory Conditionsmentioning
confidence: 99%